Turkey : Sixth and Seventh Review Under the Stand-By Arrangement; Staff Supplement; and Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Turkey showed good macroeconomic performance under the Stand-By Arrangement. Executive Directors stressed the need to maintain strong fiscal and monetary policies, and accelerate structural reforms. They appreciated the authority's efforts to reestablish the fiscal solvency and the adoption of the new central bank law. They agreed that the full implementation of the economic program would help restore macroeconomic stability and address the structural root causes of the country's problems, thereby laying the foundations for the resumption of growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet